Processes of community change and social action - Omoto, Allen Martin (Claremont symposium on applied social psychology, 2005)
This volume, an outgrowth of the annual meeting of the Claremont Symposium on Applied Social Psychology, focuses on examples of social change and the processes at work in creating change. This volume represents a product of their cumulative insight, research results, and perspectives; it includes chapters from each of the symposium presenters as well as a few select chapters from other scholars. The chapters, when taken as a whole, present findings from rigorous and provocative programs of research that offer illuminating lessons for anyone interested in community change, civic participation, and social action. Across the chapters, topics related to service learning, social movements, political socialization, civil society, and especially volunteerism, are addressed. It is an exciting and unique collection, with contributors from different disciplines and even different subdisciplines of psychology. Specifically, the research and thinking described in these pages has been conducted by sociologists, public health researchers, social psychologists, developmental psychologists, personality-oriented psychologists, and community psychologists. Thus, from a number of different perspectives and disciplinary traditions, all of the contributors have been attempting to understand processes of community change and the effects of such efforts on the individuals involved in creating them and on society at large.